Incremental Nonlinear Dynamic Inversion Control for Hydraulic Hexapod Flight Simulator Motion Systems*. Issue 1 (July 2017) - Huang, Yingzhi; Pool, D.M.; Stroosma, O.; Chu, Q.P.
Abstract: Hydraulic driven manipulators face serious control problems due to the nonlinear system dynamics and model and parametric uncertainties of hydraulic actuators. In this paper, a novel sensor-based Incremental Nonlinear Dynamic Inversion controller is applied to force tracking control of hydraulic actuators of a hexapod flight simulator motion system, which together with an outer-loop motion tracking controller forms a motion control system. Due to the use of feedback of pressure difference derivatives, the proposed technique is not dependent on accurate model and parameters, which makes the controller inherently robust to model uncertainties. Furthermore, The sensor-based control approach is particularly suitable for hydraulic force tracking in existence of an outer-loop controller decoupling hydraulic-mechanic interaction term from the inner-loop dynamics. Simulation results indicate that the novel approach yields better tracking performance and confirm the greater robustness to model and parametric uncertainties compared with a traditional nonlinear dynamic invention approach.